BACTERIOLOGICAL DIVERSITY OF THE ORGANS OF Clarias gariepinus, Chrysichthys nigrodigitatus, AND Oreochromis niloticus FROM KATSINA-ALA AND IBI RIVERS - UMMA , S. B; UJAH, S.; GANI, B.; AGU, R. Z. (Nigerian Journal of Fisheries, 2023)
Knowledge of the bacteriological load of fish is important for public health as fish are easily susceptible to bacterial attack due to their nature. Therefore, this study aimed at assessing the relative microbial loads of gills, intestine, and skin of Oreochromis niloticus, Chrysichthys nigrodigitatus, and Clarias gariepinus from Katsina Ala and Ibi Rivers. Targeted fishes (n= 120) were randomly collected from fishermen at the landing sites, grouped and aseptically transported alive using oxygenated nylon bags to Microbiology Laboratory for bacteriological assay using standard procedures. Aseptically, spread and pour plate methods were carried out for gills, intestinal samples and skin respectively. Bacterial loads from the organs of the fishes in both locations were significantly different (P ˂ 0.05). Specifically, the gills of Oreochromis niloticus had significantly more bacterial load than Chrysichthys nigrodigitatus and Clarias gariepinus. Similarly, the intestine and skin of Clarias gariepinus had more bacterial loads. In comparison, total bacterial viable counts (CFU/g) of the gills for Chrysichthys nigrodigitatus and Oreochromis niloticus were significantly higher in Ibi River, same for the intestine and skin of Oreochromis niloticus. Generally, bacteriological loads of the targeted fishes were higher in Ibi River; however, in some instance they were below the acceptable limits for food safety.